Conservación de los Antecedentes Penales y Policiales de los Menores de 18 años y mayores de 14 que han cometido Delitos Comunes - Flores Carrillo, Betty Leonor (2017)
The theme and problem called "Conservation and Police Criminal record of under 18 years old and over 14 common to have Committed Crimes" is a problem of reality and is related to juvenile delinquency. Ecuadorian law defends physical development and personality of children and adolescents to the point that has regulated its history and criminal record is provisional it has to be destroyed once it has reached 18 years and acquires its full capacity as citizen. This reality has allowed investigate the legal reasons for this suppression of the historical past of the crimes of children and adolescents but according to reality and the services provided by the state are mandatory custody and we have therefore raised the conservation of archives children and adolescents who have committed crimes because they serve for research purposes and for national security, we know that the end files under society gains nothing but instead to remain in custody has great utility and for policies public, monitoring and control breaches of the criminal regime that is produced in the country, this of course requires reforms to normativities to comply with the principle of legality because they are actions that are part of public law. By destroying these files with the criminal and police records of minors we are helping the proliferation and criminal rise of adolescents, since at the time of not recording a history where the conflict that they kept with the law was evidenced are being given free pass To the criminal continuation and thus leave in helplessness the citizens who are the most affected.